Pemberdayaan Usaha Maz Zakki Tahun Pada Badan Amil Zakat Nasional Kota Yogyakarta - Bandoko Bandoko; A Turmudzi; M.N.K Al Amin (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
The productive economic empowerment program of the Badan Amal Zakat at Yogyakarta City (BAZKY) in 2017 is Maz Zakki which is different from its implementation in the previous year. Through qualitative research by collecting data through in-depth interviews, observation and documentation, it can be seen that BAZKY has provided zakat funds to poor citizens in the form of money for business with business coaching, mentoring, and monitoring. The results of the evaluation show that the implementation process, starting from preparation, implementation and supervision, still follows the national zakat management rules and regulations. Even BAZKY, through Mas Zakki, has provided ongoing assistance in the form of merchant schools after selecting them with direct visits to the homes of prospective recipients of business fund assistance. This is also a form of monitoring and supervision of business sustainability. Such implementation has met the provisions of the current Zakat Management Law in Indonesia. This is stated in Law 23 of 2011 concerning Management of Zakat. This is where the legal rules regarding zakat management organizations at the level of BAZNAS and LAZ are elaborated.